Quantitatively defining the conservation status of Natura 2000 forest habitats and improving management options for enhancing biodiversity - Hernando, Ana; Tejera, Rosario; Velazquez, Javier; Núñez, María Victoria (Biodiversity and Conservation, 2010)
The main goal of Natura 2000 network is to guarantee the favourable conservation status of habitats and species ensuring European biodiversity. As a result, certain forest areas have been included in this network listed as 9230-Quercus pyrenaica habitat and 9340-Quercus ilex subsp. rotundifolia forest habitat. These areas were previously used for ﬁrewood extraction or livestock grazing and browsing. Nowadays these habitats are coppice forests with asexual regeneration, which is far from the desired conservation status. Traditional timber harvesting plans do not take account of the new objectives required for these Natura sites, which attempt to ensure biodiversity and recreational uses instead of simply focusing on timber production. This paper proposes a ﬂexible methodology (applied to the study area ‘‘Dehesa Boyal’’ in A´ vila, Spain) for managing Natura 2000 forest sites by stands for sustainable forest management and the new requirements. The methodology has two phases. The ﬁrst, ‘‘Division of the forest area into stands’’, deﬁnes homogeneous patches of vegetation distinct in species composition, physiognomic structure and future management. The second, ‘‘Conservation status assessment of stands’’, quantiﬁes the conservation status of each previously classiﬁed stand considering a series of factors such as: functional health, restoration, ﬂoral richness and structure. A total value integrating the conservation status of stands is then calculated for the habitat. Both phases use Geographic Information System tools for managing information and visualizing results. The proposed methodology provides forest managers with a good knowledge of the territory and subsequently enables them to take appropriate conservation measures to maintain biodiversity.
Keywords: Adaptive management; Asexual regeneration; Cattle; Coppice forest; GIS; Mediterranean biogeographic region; oak; Quercus pyrenaica; Spain; Stand

Description of Tuber malenconii mycorrhizae and a comparison with mycorrhizae of T. aestivum and T. mesentericum - Garcia-Montero, Luis G.; Di Massimo, Gabriella; Manjon, Jose L.; Velazquez, Javier (MYCOTAXON, 2008)
Tuber malenconii is a recently described uncommon European truffle associated with Quercus ilex that is potentially detrimental to the cultivation of the highly prized edible, T. melanosporum. Examination of T. malenconii mycorrhizae synthesized from fresh ascocarps revealed polygonal mantle cells and numerous cystidia with basal-forked ramifications. Differences between T. malenconii, T. mesentericum, and T. aestivum mycorrhizae are noted; compound and scanning electron micrographs provide additional comparisons.
The following values have no corresponding Zotero field: pub-location: PO BOX 264, ITHACA, NY 14851-0264 USA publisher: MYCOTAXON LTD
Keywords: Ectomycorrhizae; hypogeous fungus; Tuberaceae

Description of Tuber malenconii mycorrhizae and a comparison with mycorrhizae of T. aestivum and T. mesentericum (MYCOTAXON, 2008)
Tuber malenconii is a recently described uncommon European truffle associated with Quercus ilex that is potentially detrimental to the cultivation of the highly prized edible, T. melanosporum. Examination of T. malenconii mycorrhizae synthesized from fresh ascocarps revealed polygonal mantle cells and numerous cystidia with basal-forked ramifications. Differences between T. malenconii, T. mesentericum, and T. aestivum mycorrhizae are noted; compound and scanning electron micrographs provide additional comparisons.